Pengaruh Model Pembelajaran berbasis Masalah terhadap Kemampuan Berpikir Kritis - Widayati, Sri; Khofifah, Eliyani Nur (Faculty of Teacher Training and Education of Undaris, 2022)
Critical thinking skills in students need to be developed in the learning process. Teachers have a strategic role in choosing the approach and learning method used. One of the learning models that can train students' critical thinking skills is a problem-based learning model or Problem Based Learning (PBL). Implementing problem solving skills must be possessed by students in the 21st century, can train students' abilities in problem solving in everyday life. The purpose of this study was to determine the effect of problem-based learning models on students' critical thinking skills. This type of quasi-experimental research (Quasi Experiment). The subjects of this study were 52 students of class X SMK NU Ungaran for the 2021/2022 academic year majoring in Visual and Communication Design (DKV). The results of hypothesis testing in this study using the biserial correlation test with the results of a significance value smaller than the alpha value applied, namely 0.050. The significance value of the data test is 0.010 < 0.050, and in the test using the t test, the t-count results obtained are 4.501 which is greater than the t-table of 2.008 (4.501> 2,000) and the significance obtained is 0.000 < 0.050. This means that problem-based learning model learning can foster critical thinking skills.Keywords: problem-based learning model, critical thinking skills